PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN GAYA KEPEMIMPINAN SITUASIONAL TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA KANTOR DESA MAILEPPET, KECAMATAN SIBERUT SELATAN, KABUPATEN KEPULAUAN MENTAWAI - Alan Fernando; Rosita Bangun; Dede Ansyari Guci (Mount Hope Management International Journal, 2024)
This study aims to provide empirical evidence of the influence of transformational leadership style and situational leadership style on employee performance, with job satisfaction as a mediating variable at the Maileppet Village Office, South Siberut District, Mentawai Islands Regency. This research adopts a quantitative approach, with data analysis conducted using Path Analysis through the SPSS version 29 program. The results of the study indicate that: 1). Transformational leadership style has a positive and significant effect on employee performance. 2). Situational leadership style has a positive and significant effect on employee performance. 3). Transformational leadership style has a positive and significant effect on job satisfaction. 4). Situational leadership style has a positive and significant effect on job satisfaction. 5). Job satisfaction has a positive and significant effect on employee performance. 6). Transformational leadership style has a positive and significant effect on employee performance with job satisfaction as a mediating variable. 7). Situational leadership style has a positive and significant effect on employee performance with job satisfaction as a mediating variable.